Trunk function and its relationship with sagittal spinopelvic alignment in a 6-year prospective community-based cohort - Kobayashi, Tetsuya; Imai, Mitsuru; Chiba, Hisashi (Journal of Spine Research, 2022)
Introduction: The purpose of this study was to investigate trunk function and its relationship with sagittal spinopelvic alignment in a 6-year prospective community-based female cohort.Methods: A total of 89 healthy female subjects were recruited since 2010. All the subjects were followed over a five-year period. Mean age was 65.2 years at baseline and 71.3 years at follow-up, and the mean follow-up period was 6.1 years. Upright whole spine radiographs were used to evaluate sagittal spinopelvic parameters including sagittal vertical axis (SVA), thoracic kyphosis, lumbar lordosis (LL), sacral slope (SS), pelvic tilt (PT), and pelvic incidence. Clinical evaluations included trunk flexor (FX) and extensor (EX) muscle strength using isometric device, lumbar range of motion (ROM), trunk inclination angle at standing (sTIA) and at gait posture (gTIA), functional reach test, body mass index, visual analogue scale (VAS) of back pain, and HRQOL. The results were analyzed using paired t test or Wilcoxon test.Results: Longitudinal changes, shown as baseline/follow-up (p value), were as follows: FX 289N/235N (p<0.001), EX 498N/471N (p=0.036), sTIA 3.9/6.2 degrees (p<0.001), and gTIA 7.7/10.4 degrees (p<0.001). VAS and HRQOL changes were not significant. Radiographically, SVA (p<0.001) and PT (p=0.013) increased significantly, while LL (p<0.001) and SS (p=0.010) decreased significantly at follow-up.Conclusions: Longitudinal data from this study showed reduction of trunk muscle strength, postural inclination, and kyphotic spinopelvic alignment. Adult spinal deformity developed in parallel with reduction of trunk muscle strength and ambulatory controls. Physical characteristics should be an important factor as well as radiographic parameters.